The Plastic Bottle as a Market Device: A PRISMA Systematic Review of Sustainable Packaging, Environmental Awareness, and Consumer Purchase Intention - Nunung Nurnilasari; Annita Jannah; Darwanto Darwanto; Yuliana Saryip Wijayanti (International Journal of Management Science and Application, 2026)
The single-use plastic water bottle represents a highly optimized market device that has successfully commodified a vital public resource. However, its immense convenience generates severe environmental externalities, leading to a corporate shift towards sustainable packaging alternatives. Although empirical studies on eco-friendly packaging are rapidly expanding, a comprehensive synthesis of how these material changes structurally activate consumer psychology is lacking. This systematic literature review employs the PRISMA guideline to evaluate and synthesize current academic evidence regarding the repercussion of sustainable packaging on consumers willingness to buy, specifically examining the mediating role of environmental awareness. A systematic search of major digital databases (including Scopus and Web of Science) was performed for peer-reviewed studies published between 2016 and 2026. Applying strict inclusion and exclusion criteria, a final pool of relevant empirical articles was selected and qualitatively synthesized. The synthesis reveals that while sustainable packaging changes (such as rPET and bioplastics) act as critical structural visual cues, their direct effect on purchase intention is highly volatile and bounded by price premiums. Importantly, the literature consistently identifies environmental awareness as a key psychological mediator; sustainable packaging attributes are most effective when they successfully trigger a consumer’s internal eco-consciousness and situational guilt. This research straddles the disciplines of economic sociology and green marketing, as it re-theorizes the sustainable bottle, not simply as a container, but as a pedagogical market device. The results offer managerial implications to beverage manufacturers for optimizing eco-branding strategies and policy-makers evidence to support extended producer responsibility frameworks.